Extensive Genetic Connectivity and Historical Persistence Are Features of Two Widespread Tree Species in the Ancient Pilbara Region of Western Australia - Nistelberger, Heidi M. (Genes (Basel), 2020)
Phylogeographic studies can be used as a tool to understand the evolutionary history of a landscape, including the major drivers of species distributions and diversity. Extensive research has been conducted on phylogeographic patterns of species found in northern hemisphere landscapes that were affected by glaciations, yet the body of literature for older, unaffected landscapes is still underrepresented. The Pilbara region of north-western Australia is an ancient and vast landscape that is topographically complex, consisting of plateaus, gorges, valleys, and ranges, and experiences extreme meteorological phenomena including seasonal cyclonic activity. These features are expected to influence patterns of genetic structuring throughout the landscape either by promoting or restricting the movement of pollen and seed. Whilst a growing body of literature exists for the fauna endemic to this region, less is known about the forces shaping the evolution of plant taxa. In this study we investigate the phylogeography of two iconic Pilbara tree species, the Hamersley Bloodwood (Corymbia hamersleyana) and Western Gidgee (Acacia pruinocarpa), by assessing patterns of variation and structure in several chloroplast DNA regions and nuclear microsatellite loci developed for each species. Gene flow was found to be extensive in both taxa and there was evidence of long-distance seed dispersal across the region (pollen to seed ratios of 6.67 and 2.96 for C. hamersleyana and A. pruinocarpa, respectively), which may result from flooding and strong wind gusts associated with extreme cyclonic activity. Both species possessed high levels of cpDNA genetic diversity in comparison to those from formerly glaciated landscapes (C. hamersleyana = 14 haplotypes, A. pruinocarpa = 37 haplotypes) and showed evidence of deep lineage diversification occurring from the late Miocene, a time of intensifying aridity in this landscape that appears to be a critical driver of evolution in Pilbara taxa. In contrast to another study, we did not find evidence for topographic features acting as refugia for the widely sampled C. hamersleyana.